(untitled) (The International Journal for Scientific Research, 2025)
This academic paper elucidates that cognitive functioning in any domain — memory, attention, abstract reasoning, language, etc. — cannot be uniquely correlated to either the left or right cerebral hemispheres. These complex actions stem from both hemispheres of the brain working together and in coordination with one another as a team, emphasizing their relationship. The localization of language has been the subject of decades of research, and the aim of this extensive article is to identify not only the different distribution of language across the two hemispheres but also their respective anatomical locales. More on this integrative view of connectionism will be discussed here, as it provides a very different and opposes the classical localizationist paradigm, wherein it has further divided many brain regions into their respective and exclusive functions and was thus supported by this convincing and comprehensive study. This study seeks to shed light on essential concepts related to a host of language features associated with several interconnected brain regions. We hope that this article will provide a significant contribution to the ongoing discussions within the field of cognitive neuroscience and provide insight into our understanding of language processing and its brain bases.